2017
DOI: 10.1016/j.jcin.2017.07.044
|View full text |Cite
|
Sign up to set email alerts
|

Association of Chronic Kidney Disease With In-Hospital Outcomes of Transcatheter Aortic Valve Replacement

Abstract: Patients with CKD or ESRD have worse in-hospital outcomes after TAVR. AKI is associated with higher in-hospital mortality in patients undergoing TAVR and the incidence of AKI has not declined over the years.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
90
3

Year Published

2019
2019
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 120 publications
(105 citation statements)
references
References 24 publications
12
90
3
Order By: Relevance
“…After adjusting for patients' demographics, clinical presentation (intermittent claudication vs. CLI), comorbidities, insurance and socioeconomic status using multivariate regression mode, ESRD patients on dialysis remained at higher risk of in‐hospital mortality (adjusted OR: 2.13 [95% CI: 2.04–2.23]; Table ). Risk‐adjusted linear regression for LOS demonstrated a statistically significant longer LOS in the ESRD dialysis group (median LOS = 7 days; Interquartile range [IQR]) when compared with those with normal kidney function (median LOS = 3 days; [IQR; 0–6]; p < .001).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…After adjusting for patients' demographics, clinical presentation (intermittent claudication vs. CLI), comorbidities, insurance and socioeconomic status using multivariate regression mode, ESRD patients on dialysis remained at higher risk of in‐hospital mortality (adjusted OR: 2.13 [95% CI: 2.04–2.23]; Table ). Risk‐adjusted linear regression for LOS demonstrated a statistically significant longer LOS in the ESRD dialysis group (median LOS = 7 days; Interquartile range [IQR]) when compared with those with normal kidney function (median LOS = 3 days; [IQR; 0–6]; p < .001).…”
Section: Resultsmentioning
confidence: 99%
“…Patients with normal kidney function was defined as those who did not have CKD, ESRD requiring dialysis, renal transplant, or acute kidney injury. This approach has been used by previous studies using the NIS database to accurately identify patients with PAD and CLI undergoing PVI, and those with ESRD on dialysis …”
Section: Methodsmentioning
confidence: 99%
“…However, most studies conducted prior to Hansen et al found this association insignificant. The association between stage 4 or 5 CKD and increased mortality was reported as significant in later studies . However, several studies did not report significant association between CKD and risk of mortality in TAVR patients .…”
Section: Discussionmentioning
confidence: 96%
“…The association between stage 4 or 5 CKD and increased mortality was reported as significant in later studies. 19,20,[25][26][27][28] However, several studies did not report significant association between CKD and risk of mortality in TAVR patients. [29][30][31] Our meta-analysis demonstrated the association between CKD and 30-day overall mortality, 30-day cardiovascular mortality, long-term cardiovascular mortality, and long-term overall mortality.…”
Section: Discussionmentioning
confidence: 99%
“…Especially in combination with other cardiovascular risk factors, CKD might render AF patients ineligible for long-term OAC and might favour LAAC in many of these patients. However, renal failure was also shown to increase the rate of periprocedural complications in cardiac interventions and to worsen the outcome [10,11]. Currently, outcome data on LAAC in CKD patients are limited [12].…”
Section: Introductionmentioning
confidence: 99%